TLR7 Is Critical for Anti-Viral Humoral Immunity to EV71 Infection in the Spinal Cord - Lin, Ya-Lin; Lu, Mei-Yi; Chuang, Chi-Fen; Kuo, Yali; Lin, Hong-En; Li, Fu-An; Wang, Jen-Ren; Hsueh, Yi-Ping; Liao, Fang (Frontiers in Immunology, 2021)
Enterovirus 71 (EV71) is a positive single-stranded RNA (ssRNA) virus from the enterovirus genus of Picornaviridae family and causes diseases ranged from the mild disease of hand, foot and mouth disease (HFMD) to the severe disease of neurological involvement in young children. TLR7 is an intracellular pattern recognition receptor (PRR) recognizing viral ssRNA. In this study, we investigated the role of TLR7 in EV71 infection in mouse pups (10-12 days old) and found that WT and TLR7KO mice infected with EV71 show similar limb paralysis at the onset and peak of the disease, comparable loss of motor neurons, and similar levels of antiviral molecules in the spinal cord. These results suggest that TLR7 is not the absolute PRR for EV71 in the spinal cord. Interestingly, TLR7KO mice infected with EV71 exhibit significantly delayed recovery from limb paralysis compared with WT mice. TLR7KO mice infected with EV71 show significantly decreased levels of IgM and IgG2, important antibodies for antiviral humoral immunity. Furthermore, TLR7KO mice infected with EV71 show a decrease of germinal center B cells in the spleen compared with WT mice. Altogether, our study suggests that TLR7 plays a critical role in anti-viral humoral immunity rather than in being a PRR in the spinal cord during EV71 infection in young mice.